High perennial ryegrass seeding rates reduce plant size and survival during the first year after sowing: does this have implications for pasture sward persistence?. (12th August 2016) - Lee, J. M.; Thom, E. R.; Wynn, K.; Waugh, D.; Rossi, L.; Chapman, D. F.
Abstract: Failure of perennial ryegrass swards to persist is a key issue on dairy farms in many areas of the world. This study describes an experiment conducted to test the hypothesis that high ryegrass seeding rates (>18 kg seed ha −1 ) reduce plant size and physical survival during the first year after sowing, with negative implications for population persistence. Four cultivars representing four functional types of perennial ryegrass were sown at five seeding rates (equivalent to 6, 12, 18, 24 and 30 kg seed ha −1 ) with white clover in three dairying regions of New Zealand. Plant establishment rates, size and survival were measured for the first 13 months after sowing. Herbage accumulation, botanical composition and perennial ryegrass tiller density were also monitored. Increasing seeding rate reduced plant survival in the seven weeks after sowing, reflecting likely differences in germination and very early mortality of small seedlings. Thereafter, plant survival was relatively high and consistent across seeding rates at two sites but was consistently greater in the 6 kg ha −1 treatment compared with the 24 and 30 kg ha −1 treatments at one site. Higher seeding rates also increased ryegrass tiller density and the contribution of ryegrass towards total herbage biomass but reduced the contribution of white clover. Very few cultivar × seeding rate interactions were detected for any of the measured variables. Many of the seeding rate effects dissipated by the end of the first year after sowing, indicating that high seeding rates did not predispose swards to poor persistence in the longer term, irrespective of ryegrass functional type.